The Treatment of History in Anna z Radziwiłłów Mostowska’s Novel Astolda. Between Historical, Gothic, and Sentimental Fiction - Petronienė, Jūratė (Colloquia, 2026)
The article discusses the treatment of history in Anna z Radziwiłłów Mostowska’s (Ona Radvilaitė-Mostovskienė) historical novel Astolda (Astolda, Xiężniczka z krwi Palemona, pierwszego Xiążecia litewskiego, czyli nieszczęśliwe skutki namiętności. Powieść oryginalna z historii litewskiej, 1807). Drawing on the theory of the historical novel genre, it examines a distinctive use of Lithuanian history conditioned by the literary landscape of early nineteenth-century Lithuania (Mostowska revives the myth of Palemon, a story about the noble Lithuanian origin from the Romans, depicting the transition from paganism to Christianity), as well as a providentialist view of the flow of history as an eternal cycle in which moments of glory and decline give turn to each other. The characteristics of Mostowska’s authorship as one of the first female writers in Lithuania also become visible: free experimentation with the conventions of the pre-Scott historical novel genre and a desire to meet the expectations placed on female writers and to question women’s status in the society of the time. Elements of the historical, Gothic, and sentimental novel intertwine in Mostowska’s novel Astolda. Although the work belongs to the pre-Scott historical novel, the depiction of history is not merely decorative but serves a deeper function: Astolda goes beyond the boundaries of the pseudo-historical novel genre.
Keywords: Anna z Radziwiłłów Mostowska (Ona Radvilaitė-Mostovskienė); nineteenth-century Lithuanian women’s literature; historical novel; Gothic novel; sentimental novel; the myth of Palemon